ANALISIS KUALITAS PELAYANAN MELALUI METODE E-SERVQUAL UNTUK MENGETAHUI KEPUASAN KONSUMEN E-COMMERCE SHOPEE PADA MASYARAKAT KOTA SUKABUMI - Firman, Arief; Nurapipah, Dina; Komharudin, Komharudin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the analysis of service quality on Shopee customer satisfaction in Sukabumi City. This study uses a service quality model, namely E-ServQual which has seven dimensions, namely, efficiency, reliability, fulfillment, privacy, responsiveness, compensation, and contact. This study uses quantitative methods. The data collection technique used is by distributing questionnaires to obtain primary data, while secondary data is obtained from literature studies. This questionnaire consists of consumer perceptions and expectations. The tests carried out are validity tests and reliability tests which are then carried out by calculating the gap. The calculation results show that the seven dimensions have a negative gap value with three dimensions with the largest gap value, namely the dimensions of compensation, fulfillment and responsiveness, this means that service quality has not met shopee customer satisfaction. The results of this study indicate that the research results contribute to the quality of shopee services in Indonesia and customer satisfaction can be used as input or consideration in developing strategies in the future